Sistema de gestão de ativos imobilizados do Instituto do Patrimônio Histórico e Artístico Nacional (IPHAN): ênfase em tangível permanente e consumo. Pesquisa, análise e proposta de implantação - Dornelles, Daniela Fernandes (2015)
The convergence of international accounting standards in Brazil brought great advances and contributions to the improvement of accounting reports. Regarding the issue of fixed assets, is that this work intends to present the issues related to management and also examine the importance assumed by the adoption of certain tools for their control and management. In the wake of the debate on the strategic role played by accounting, introduces the theme of the importance of active asset management in public organizations for the success of the registration and control of these assets. Finally, explore the possibilities for efficient and effective management proposing the development and implementation of one of Fixed Assets Management System that meets the Historical Heritage Institute for National Artistic (IPHAN).